The golden doves eaudiobook A novel. - Kelly, Martha Hall (Books on Tape, 2023)
Two female spies risk everything to hunt down an infamous Nazi in this sweeping, profound tale of bravery from the bestselling author of Lilac Girls . “A riveting story of two brave and amazing women who work in the French resistance during World War II . . . a triumph!”—Lisa Scottoline, New York Times bestselling author of Eternal American Josie Anderson and Parisian Arlette LaRue are thrilled to be working in the French resistance, stealing so many Nazi secrets that they become known as the Golden Doves, renowned across France and hunted by the Gestapo. Their courage will cost them everything. When they are finally arrested and taken to the Ravensbrück concentration camp, along with their loved ones, a reclusive Nazi doctor does unspeakable things to Josie’s mother, a celebrated Jewish singer who joined her daughter in Paris when the world seemed bright. And Arlette’s son is stolen from her, never to be seen again. A decade later the Doves fall headlong into a dangerous dual mission: Josie is working for U.S. Army Intelligence and accepts an assignment to hunt down the infamous doctor, while a mysterious man tells Arlette he may have found her son. The Golden Doves embark on a quest across Europe and ultimately to French Guiana, discovering a web of terrible secrets, and must put themselves in grave danger to finally secure justice and protect the ones they love. Martha Hall Kelly has garnered acclaim for her stunning combination of empathy and research into the stories of women throughout history and for exploring the terrors of Ravensbrück. With The Golden Doves, she has crafted an unforgettable story about the fates of Nazi fugitives in the wake of World War II—and the unsung female spies who risked it all to bring them to justice.